The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10815-010-9395-6
|View full text |Cite
|
Sign up to set email alerts
|

Activin A inhibits activation of human primordial follicles in vitro

Abstract: Purpose To determine whether Activin A affects the activation and survival of human primordial follicles in vitro. Methods Ovarian cortical biopsies from eight women undergoing elective caesarean sections or benign gynaecological procedures were taken and cut into small pieces (1-3 mm 3 ), cultured in serum-free medium for 7 days with/without human recombinant Activin A at a concentration of either 50 or 100 ng/ml. Ovarian tissue were analysed by histology for follicle viability, development and density. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…The authors suggest that activin may play an inhibitory role in the recruitment and activation of primordial follicles in humans. However, in our analyses of ActA action, primordial follicles were neither stimulated nor inhibited in these processes using the same concentration of activin as reported by Ding et al (2010). Our analyses revealed that FSH decreased apoptosis occurring in vitro in the primordial follicle pool (14 vs 38%), supporting our Table 1 Proportion of follicle class represented as a percentage of total follicle numbers from day 4 fresh ovaries (before 10 days of culture) and all treatment groups (after 10 days of culture).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The authors suggest that activin may play an inhibitory role in the recruitment and activation of primordial follicles in humans. However, in our analyses of ActA action, primordial follicles were neither stimulated nor inhibited in these processes using the same concentration of activin as reported by Ding et al (2010). Our analyses revealed that FSH decreased apoptosis occurring in vitro in the primordial follicle pool (14 vs 38%), supporting our Table 1 Proportion of follicle class represented as a percentage of total follicle numbers from day 4 fresh ovaries (before 10 days of culture) and all treatment groups (after 10 days of culture).…”
Section: Discussionmentioning
confidence: 67%
“…However, when compared with day 4 fresh ovaries, there was a significant decrease in primordial follicle number (P!0.001) consistent with follicle activation in vitro. Studies by Ding et al (2010) showed that ActA had a dose-dependent inhibitory effect on the activation of human primordial follicles in vitro. The authors suggest that activin may play an inhibitory role in the recruitment and activation of primordial follicles in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, studies using mouse genetic models, in vivo injection, and ex vivo organ culture approaches have demonstrated that many TGF-b superfamily and signaling proteins mediate the early stages of folliculogenesis. These studies have indicated that several key family members, including AMH, activin, inhibin, BMP-4, and BMP-7, are important for the primordial to primary follicle transition [31][32][33][34] and that Smad proteins are essential for primordial germ cell development and folliculogenesis [35]. In accord with these findings showing that the TGF-b signaling pathway is critical for primordial FIG.…”
Section: Mirnas Regulate Early Follicle Developmentmentioning
confidence: 85%
“…In vitro culture experiments were conducted using thawed ovarian samples from 5 patients, presenting the higher number of follicles according to the previous histological examination. As shown in previous studies, culture of ovarian pieces allows cellular interactions between follicles and surrounding stroma indispensable to sustain follicular growth initiation [8,25,34]. In order to retain the 3D structure of the follicles, a low-attachment culture system limiting stroma cell adhesion on the culture support was used.…”
Section: Discussionmentioning
confidence: 99%